Trenchless Replacement of Buried Cable Lines - Hans-Joachim Bayer (Acta Montanistica Slovaca, 2007)
An enormous amount of underground electricity and telecommunication cables have been worn over the time with technical defects or need capacity increases. Thus, new lines need to be installed. In urban areas, even in smaller communities and in natural reserves, open trenching is difficult and often not permitted.In response, new patented methods of trenchless cable replacement using the HDD equipment have been developed by the TT Group. The new technology is called “Wash-over-cable-replacement” and applies specially designed drill heads, cutting around the old cable string in various configurations (completely closed, U-shape or S-shape embracing), depending to the coating type of the old cable. This special cable replacement drill head separates the cable from the surrounding adhesive soil or the sand bedding by creating a very small annular space around the cable thus enabling the pulling or dragging out of the old cable section between the start and the exit pit. After the old cable has been loosened from the surrounding soil by means of the wash over process and pulled out, the new cable can be smoothly pulled into the void using the drill rods and embedding the new cable in a rich bed of Bentonite.The wash-over drill heads are slim and have inner and outer nozzles for Bentonite and bits to handle roots, pebbles, gravel and the like. These drill heads perform very quickly (up to 3 meters per minute) to effectively wash over existing cables without damaging the cable coating and prepare the ground for a fast new laying of a new cable in the existing line. Network owners also benefit from the fact that new geodetic or topographic surveys and documentations of the new cable are not necessary. Only the documents, remarks, technical codes and existing geodetic data need to be updated.The paper will outline the technological background and include several practical job examples.